Toleration by Victimized Coffeeshops in Amsterdam - Jacques, Scott (2021)
Dutch coffeeshops are quasi-illegal. Their sale of cannabis is de jure prohibited but de facto permitted. In this sense, their criminal acts are tolerated. Less often explored, and less well understood, is that coffeeshops also tolerate crimes against them. “Doing nothing” is a common way to manage drug market conflict. Why and how does it occur? Research has not focused on that question. In this article, we use the opportunity and rationality perspectives to analyze qualitative data obtained during interviews with 50 personnel of coffeeshops in Amsterdam, the Netherlands. After presenting our findings, we discuss their similarities to, and divergences from, what is known about toleration among fully-illegal dealers